2021
DOI: 10.2147/ndt.s297504
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Treatment of Chronic Insomnia: A Narrative Review of New Nonpharmacologic and Pharmacologic Therapies

Abstract: Chronic insomnia disorder, which affects 6–10% of the population, is diagnostically characterized by ongoing difficulties with initiating or maintaining sleep occurring at least three times per week, persisting for at least 3 months, and associated with daytime impairment. While chronic insomnia is often considered a condition primarily related to impaired sleep, the disorder can also adversely affect domains of physical and mental health, quality of life, and daytime function, which highlights the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 142 publications
0
31
0
2
Order By: Relevance
“…Davidson et al (2019) concluded that a sleep program with stimulus control and sleep restriction based on behavioral components showed better effects on sleep latency and awakenings after the onset of sleep, as well as on the general reduction in severity evaluated with the ISI scale. Cognitive components have also been shown to be effective in reducing insomnia by facilitating the identification and modification of dysfunctional thoughts, redirection of unrealistic expectations and misperceptions of sleep, elimination of worry, and modification of attentional bias (Harvey et al, 2014;Rosenberg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Davidson et al (2019) concluded that a sleep program with stimulus control and sleep restriction based on behavioral components showed better effects on sleep latency and awakenings after the onset of sleep, as well as on the general reduction in severity evaluated with the ISI scale. Cognitive components have also been shown to be effective in reducing insomnia by facilitating the identification and modification of dysfunctional thoughts, redirection of unrealistic expectations and misperceptions of sleep, elimination of worry, and modification of attentional bias (Harvey et al, 2014;Rosenberg et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Baduanjin exercise is a traditional Chinese exercise that can improve the function of the internal organs of the body by regulating the flow of Qi and blood through the meridians to achieve the effect of fitness and dispel diseases [20] . At present, Baduanjin exercise has been widely used in the treatment of diabetes mellitus, [21] chronic obstructive pulmonary disease, [22] and heart failure, [23] and has achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…2,16 This misperception has contributed to significant undertreatment of sleep disturbances. 10 In the DSM-5, however, the distinction between primary and secondary insomnia was eliminated, and the term insomnia disorder was adopted. Insomnia disorder is therefore now recognized as a condition that often coexists with, and is not merely secondary to, another condition such as depression.…”
Section: The Importance Of Comorbid Insomnia In Psychiatric and Medic...mentioning
confidence: 99%